2023
DOI: 10.1021/acs.jpca.3c01298
|View full text |Cite
|
Sign up to set email alerts
|

Initial Decomposition of DATB Induced by an External Electric Field

Abstract: 1,3-Diamino-2,4,6-trinitrobenzene (DATB), a nitro aromatic explosive with excellent properties, can be detonated by an electric field. Using first-principles calculation, we have investigated the initial decomposition of DATB under an electric field. In the realm of electric fields, the rotation of the nitro group around the benzene ring will cause deformation of the DATB structure. Furthermore, when an electric field is applied along the [100] or [001] direction, the C4–N10/C2–N8 bonds initiate decomposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…As shown in Figure , the charge of β-HMX molecules in the periodic potential field of the crystal changes symmetrically with the change of the external electric field, but the charge of a single β-HMX molecule is not symmetrical with the change of the external electric field, which is why their dipole moments are different. By comparing with the dipole moment changes of other energetic materials under the electric field under this method and comparing with the dipole moment obtained by adding an electric field along the Y -axis to a single β-HMX molecule in the amorphous periodic potential field (Table ), we believe that the symmetry of β-HMX molecules and the periodic potential field composed of β-HMX crystals make the molecular dipole moment of β-HMX still 0 after adding a certain external electric field. Therefore, for the β-HMX crystal with an external electric field, the total dipole moment of the molecule is difficult to judge the change of its sensitivity.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure , the charge of β-HMX molecules in the periodic potential field of the crystal changes symmetrically with the change of the external electric field, but the charge of a single β-HMX molecule is not symmetrical with the change of the external electric field, which is why their dipole moments are different. By comparing with the dipole moment changes of other energetic materials under the electric field under this method and comparing with the dipole moment obtained by adding an electric field along the Y -axis to a single β-HMX molecule in the amorphous periodic potential field (Table ), we believe that the symmetry of β-HMX molecules and the periodic potential field composed of β-HMX crystals make the molecular dipole moment of β-HMX still 0 after adding a certain external electric field. Therefore, for the β-HMX crystal with an external electric field, the total dipole moment of the molecule is difficult to judge the change of its sensitivity.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that external electric fields (EEFs) can impact the reactivity of trigger bonds in energetic materials, thereby affecting their sensitivity. , As β-HMX is a nitro compound, the trigger bond typically involves N–NO2, , with the N1–N3 (N1′–N3′) bonds being more easily triggered. Figure shows significant changes in the N1–N3 (N1′–N3′), N2–N4 (N2′–N4′), and C2–N2 (C2′–N2′) bonds in β-HMX with increasing electric field.…”
Section: Results and Discussionmentioning
confidence: 99%
“…For all types of deformation densities, spectral decomposition of normalΔρ$$ \Delta \rho $$ can be grouped into two components concerning the corresponding eigenvalues' signs [67–70]. When analyzing deformation density, the eigenvalues have a special characteristic that allows for assigning eigenorbitals to specific occurrences.…”
Section: Computational Detailsmentioning
confidence: 99%